Gambaran Faktor Resiko Stunting Balita di Desa Siwalanpanji Kabupaten Sidoarjo Jawa Timur - Ni Luh Agustini Purnama (Malahayati Nursing Journal, 2023)
ABSTRACT Stunting is influenced by various factors that cause children's nutritional intake. The purpose of the study was to identify the risk factors for stunting in children under five in Siwalanpanji Village, Sidoarjo Regency, East Java. This research was a descriptive observational study. The population is all children under five who experience stunting at the Orchid Posyandu, Siwalanpanji Village, Sidoarjo Regency, East Java. The sampling technique used is a total sampling with a total of 30 respondents. Collecting data using a questionnaire. The results showed that 60% of stunting children got exclusive breastfeeding. All families (100%) who have stunted children with socio-economic income below the UMK (Regency Minimum Wage) Sidoarjo, which is Rp. 4,300,000. As many as 60% of stunting children tend to eat a food approach or eating behavior with the highest tendency to eat behavior indicators, namely in the category of desire to drink or the child's desire to always drink. As many as 67% of mothers who have stunted children with feeding behavior are in the poor category with the lowest aspect being providing a pleasant environment during eating  Keywords: Risk Factors, Stunting, Children  ABSTRAK Stunting dipengaruhi oleh berbagai faktor yang menyebabkan asupan gizi anak tidak seimbang. Tujuan penelitian mengidentifikasi gambaran faktor risiko kejadian stunting pada Balita di di Desa Siwalanpanji, Kabupaten Sidoarjo, Jawa Timur. Penelitiani ini adalah penelitian deskriptif observasi. Populasi semua anak usia balita yang mengalami stunting di Posyandu Anggrek, Desa Siwalanpanji, Kabupaten Sidoarjo, Jawa Timur. Tehnik sampling yang digunakan adalah total sampling dengan jumlah 30 responden. Pengumpulan data mengunakan kuesioner. Hasil penelitian menunjukkan 60% anak stunting mendapatkan ASI ekslusif. Semua keluarga (100%) yang memiliki anak stunting dengan sosial ekonomi berpenghasilan dibawah UMK (Upah Minimun Kabupaten) Sidoarjo, yaitu sebesar Rp. 4.300.000. Sebanyak 60 % anak stunting memiliki kecenderungan perilaku makan food approach atau perilaku suka makan dengan kecenderungan indikator perilaku makan tertinggi yaitu pada kategori desire to drink atau keinginan anak untuk selalu minum. Sebanyak 67% ibu yang memiliki anak stunting dengan perilaku pemberian makan dalam kategori kurang baik dengan aspek terendah pada memberikan lingkungan yang menyenangkan selama makan. Kata Kunci: Faktor resiko, Stunting, Anak